Early detection of mesenteric ischemia in critically ill patients following cardiac surgery - Zulfugar T. Taghiyev; Sophia Gunkel; Lili-Marie Beier; Carina Leweling; Kevin M. Sadowski; Borros M. Arneth; Chrysanthi Skevaki; Johannes Kalder; Paula R. Keschenau; Andreas Böning (Scientific Reports)
Abstract Mesenteric ischemia (Me-Is) is a severe complication with high mortality after cardiac surgery. We examined whether intestinal fatty acid binding protein (I-FABP) might serve as a biomarker for early detection of Me-Is following cardiac surgery. Between March 2022 and December 2023, we conducted a prospective observational study of 500 consecutive patients undergoing cardiac surgery with cardiopulmonary bypass. Blood samples were obtained at five time points perioperatively. An immunoassay was used to determine I-FABP levels in 48 individuals at high risk of Me-Is due to lactic acidosis > 4 mmol/L and interleukin (IL)-6 > 600 pg/mL: 6 patients with confirmed Me-Is (cMe-Is), 18 patients with suspected Me-Is (sMe-Is), and 24 patients a in propensity score-matched control group. Of the 48 patients, 62.5% initially had mild gastrointestinal dysfunction (AGI ≤ II), but 80% of them progressed to AGI III or higher, with 25% reaching AGI IV. Baseline serum I-FABP values were similar between the three groups. The six patients with cMe-Is showed significantly elevated serum I-FABP levels from ICU admission to 36 h post-admission, peaking at 207,411.46 pg/mL. ROC analysis identified serum I-FABP as the most accurate predictor of Me-Is, with an AUC of 0.973 at 36 h post-ICU admission (95% CI [0.764–0.997], p < 0.001) and an optimal cut-off of > 1421 pg/mL, with 100% sensitivity. In contrast, IL-6 and lactate levels showed no significant differences between groups. Serum I-FABP showed high accuracy in predicting Me-Is after cardiac surgery, outperforming IL-6 and lactate. Our data suggest that I-FABP may have value as a biomarker for early detection of Me-Is after cardiac surgery and help to improve patient management.